IMPLEMENTASI PERATURAN WALIKOTA NOMOR 28 TAHUN 2017 TENTANG PENDELEGASIAN KEWENANGAN PENYELENGGARAAN PELAYANAN TERPADU KEPADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PADANG - Puryanto Puryanto; Romiza Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In order to build an integrated economy and one-stop service, the government of Padang City issued a policy to solve these problems. The policy is managed by the Padang City Investment and One-Stop Integrated Service Office (DPMPTSP). The purpose of the DPMPTSP is to make it easier for the community to make licensing letters, in the form of a one-stop integrated service (PTSP), where PTSP provides integrated services in order to cut the bureaucracy of licensing services. Padang city. This policy is contained in the Mayor of Padang Regulation No. 28 of 2017 concerning the delegation of authority and one-stop integrated services for the City of Padang. This research uses descriptive qualitative method, with purposive sampling technique. Collecting data by library method, interview and observation. Then analyzed using the miles and huberaman methods. This study uses the theory of George C. Edward III because the indicators are in accordance with the research. The results showed that (1) the implementation of the Padang mayor's regulation no 28 of 2017 concerning the delegation of authority and one-stop integrated services in the city of Padang has not been effective, this happens because not all of the permits can be carried out by the Padang City DPMPTSP. The cause can be viewed from the elements of communication, resources, attitude of implementers and organizational structure. (2) the obstacles that occur in the implementation of Perwako No. 28 of 2017 are the lack of resources, both inadequate human resources from experts both from facilities and infrastructure resources to support the implementation of services. not yet committed to carrying out their duties. (3) efforts are being made to overcome the obstacles that occur in the implementation of Perwako No. 28 of 2017 which is to complete resources both from human resources and from facilities and infrastructure resources, then the need for a special study on the renewal of Perwako No. 28 of 2017 to better policies. . And finally, the need for DPMPTSP to fix the online service system during the corona virus 19 pandemic.